Past Obesity as well as Present Body Weight Status Is a Risk Factor for Diabetic Nephropathy - Shu Meguro; Yusuke Kabeya; Karin Tanaka; Toshihide Kawai; Masuomi Tomita; Takeshi Katsuki; Yoichi Oikawa; Yoshihito Atsumi; Akira Shimada; Masami Tanaka; Junichiro Irie; Yoshifumi Saisho; et al. (International Journal of Endocrinology)
Aims. We analyzed the prevalence of nephropathy according to past body weight status in Japanese subjects with type 2 diabetes because the influence of past obesity on diabetic complications is not certain. Methods. We examined the prevalence of nephropathy in 2927 subjects with type 2 diabetes mellitus according to current BMI and maximum BMI in the past. We defined “current obesity” as BMI on hospitalization of 25 or more, “previous obesity” as BMI on hospitalization of less than 25 and self-reported maximum BMI in the past of 25 or more, and “continuously lean” as maximum BMI of less than 25. Results. The prevalence of nephropathy was significantly higher in subjects with current obesity (40.6%) or previous obesity (35.6%) than in those who were continuously lean (24.3%) (P<0.017). In logistic regression analysis, previous obesity, as well as current obesity, was a significant risk factor for nephropathy, independent of sex, age, disease duration, hypertension, dyslipidemia, HbA1c, and diabetic retinopathy. Conclusions. Obesity in the past, as well as the present body weight status, was a risk factor for diabetic nephropathy.